2020
DOI: 10.1155/2020/8836922
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors of Radiofrequency Ablation plus Systemic Chemotherapy for Unresectable Colorectal Cancer with Liver Metastasis

Abstract: Introduction. Survival outcomes in patients with unresectable colorectal cancer (CRC) liver metastasis treated by radiofrequency ablation (RFA) combined with systemic chemotherapy and correlation with potential prognostic factors were investigated. Material and Methods. A retrospective cohort study was conducted on 61 CRC patients with unresectable liver metastasis who underwent liver tumor-directed percutaneous RFA combined with conventional systemic chemotherapy between October 2013 and September 2018. Survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The other favorable prognostic factors were 25-hydroxyvitamin D > 20 ng/mL [ 23 ] and lymphocyte-to-monocyte ratio > 3.96% [ 21 ]. Several studies have demonstrated a larger number of liver metastasis [ 10 , 15 , 16 , 26 ] and the presence of extrahepatic metastases [ 10 , 15 , 18 , 20 , 22 , 26 ] to be associated with a significantly shorter OS. The other reported negative prognostic factors were Kras mutation [ 20 ], BRAF mutation [ 11 ], intrahepatic recurrence [ 10 ], LTP at the 6-month follow-up [ 17 ], high tumor grade [ 11 ], distant metastasis at diagnosis of the primary tumor [ 11 ], and previous radiation therapy [ 11 ].…”
Section: Results In Each Type Of Primary Tumormentioning
confidence: 99%
“…The other favorable prognostic factors were 25-hydroxyvitamin D > 20 ng/mL [ 23 ] and lymphocyte-to-monocyte ratio > 3.96% [ 21 ]. Several studies have demonstrated a larger number of liver metastasis [ 10 , 15 , 16 , 26 ] and the presence of extrahepatic metastases [ 10 , 15 , 18 , 20 , 22 , 26 ] to be associated with a significantly shorter OS. The other reported negative prognostic factors were Kras mutation [ 20 ], BRAF mutation [ 11 ], intrahepatic recurrence [ 10 ], LTP at the 6-month follow-up [ 17 ], high tumor grade [ 11 ], distant metastasis at diagnosis of the primary tumor [ 11 ], and previous radiation therapy [ 11 ].…”
Section: Results In Each Type Of Primary Tumormentioning
confidence: 99%